2 Laceration of the anterior mitral valve leaflet to prevent left ventricular outflow tract obstruction (lampoon). (25th January 2018) - Khan, Jaffar M; Rogers, Toby; Babaliaros, Vasilis C; Greenbaum, Adam B; Lederman, Robert J
Abstract : Background: Left ventricular outflow tract (LVOT) obstruction is a life-threatening complication of transcatheter mitral valve implantation (TMVI), caused by septal displacement of the anterior mitral leaflet (AML). We used a new catheter technique to split the AML. Methods: Eighteen patients with severe mitral valve disease, prior surgical ring or mitral annular calcification, and prohibitive surgical risk were offered LAMPOON and TMVI on a compassionate basis. Iatrogenic LVOT obstruction was predicted in all based on echocardiography and CT. Transfemoral guiding catheters directed an electrified guidewire across the AML towards a snare in the left atrium. The externalised guidewire loop was electrified to lacerate the AML along the centreline from base to tip, sparing chordae, immediately before transseptal TMVI (figure 1). Results: All patients had successful laceration of the AML. Following TMVI, the transcatheter heart valves spanned the LVOT but with Doppler flow through the open cells. In one patient, the valve missed the anterior landing zone and deployed into the LVOT, causing obstruction despite LAMPOON. All other patients had no or tolerable gradients. Conclusions: This novel catheter technique, which resembles surgical chord-sparing AML resection, may enable TMVI in patients with prohibitive risk of LVOT obstruction. An early feasibility trial of LAMPOON is underway in the United States.